Solid-state capacitor and preparation method thereof

By optimizing the preparation method of solid-state capacitors, a dense oxide film and a three-dimensional conductive network are formed, which solves the leakage current and stability problems, realizes the reliability and consistency of high-frequency applications, and extends the service life.

CN120356788AActive Publication Date: 2025-07-22ZHAOQING BERYL ELECTRONICS TECH +1

Patent Information

Application Number
CN202510838347.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-07-22
Estimated Expiration
2045-06-23

AI Technical Summary

Technical Problem

Existing solid-state capacitors have problems such as high leakage current, insufficient stability of conductive networks and poor parameter consistency, which is difficult to meet the needs of high-frequency applications.

Method used

The core-pack winding, repair, drying, double impregnation and polymerization steps are adopted to combine the formulation optimization of the chemical liquid, impregnation liquid and oxide liquid to form a dense oxide film and a three-dimensional conductive network, and self-healing is achieved by forming a reversible borate bond with modified carbon microspheres and thiopheneol.

Benefits of technology

Reduce leakage current, improve voltage withstandability and parameter consistency, extend service life, and is suitable for high-frequency scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a solid-state capacitor and a preparation method thereof, and the preparation method comprises the following steps: (1) core package winding: interposing electrolytic paper between an anode foil and a cathode foil, and winding to form a core package; (2) a repairing step: immersing the core package into a formation liquid for repairing treatment; (3) a drying step: carrying out drying treatment on the core package in the step (2); (4) an impregnation step: immersing the core package in the step (3) into a first impregnation liquid for impregnation treatment; performing drying; immersing into a second impregnation liquid for impregnation treatment, and drying; (5) a polymerization step: immersing the core cladding in the step (4) into an oxidation liquid for polymerization; and (6) assembling, girdling and aging treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitor manufacturing, and particularly relates to a solid-state capacitor and a preparation method thereof. Background Art

[0002] As an energy storage component widely used in electronic devices, aluminum electrolytic capacitors have the advantages of low cost and high capacitance density. However, the inherent defects of their liquid electrolytes severely limit their reliability and application scenarios.

[0003] To break through the limitations of liquid capacitors, solid-state capacitors emerged by replacing liquid electrolytes with solid conductive materials, mainly divided into two categories: conductive polymer aluminum electrolytic capacitors and organic semiconductor capacitors. The solid-state structure can theoretically avoid problems such as liquid volatilization and high-frequency impedance. However, there are still significant bottlenecks in the existing technology: First, the leakage current of solid-state capacitors is generally high, and the root cause is the microscopic defects at the interface between the conductive polymer and alumina, resulting in local electric field distortion and inducing leakage conduction channels; Second, polymer materials are prone to chain segment breakage or oxidative decomposition at high temperatures, the stability of the conductive network is insufficient, and the capacitance retention rate decreases; Third, the existing impregnation process is difficult to achieve uniform compounding of solid conductive materials and cannot meet the requirements of precision circuits for parameter consistency.

[0004] In view of the above contradictions, the industry urgently needs to construct a new generation of solid-state capacitors, which can achieve precise suppression of leakage current, high-temperature self-repair ability and breakthrough in process controllability while maintaining the environmental protection and high-frequency advantages of the solid-state structure. Summary of the Invention

[0005] The purpose of this part is to outline some aspects of the embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this part, the abstract of the specification and the title of the invention of this application to avoid obscuring the purpose of this part, the abstract of the specification and the title of the invention, and such simplifications or omissions shall not be used to limit the scope of the present invention.

[0006] In view of the above and / or problems existing in the prior art, the present invention is proposed.

[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a solid-state capacitor and a preparation method thereof.

[0008] To solve the above technical problems, the present invention provides the following technical solutions: including, A preparation method of a solid-state capacitor, the preparation method comprising the following steps: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; (2) Repair step: Immerse the core package in a formation solution for repair treatment; (3) Drying step: drying the core package obtained in step (2); (4) Impregnation step: immersing the core package obtained in step (3) into a first impregnating solution for impregnation treatment; drying; immersing it into a second impregnating solution for impregnation treatment, and then drying; (5) Polymerization step: immersing the core package obtained in step (4) into an oxidizing solution for polymerization; (6) Assembling the waistband and aging treatment.

[0009] As an optimization, the density of the electrolytic paper described in step (1) is 0.45 - 0.7 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber.

[0010] As an optimization, the formation solution described in step (2) contains pure water, ammonium adipate, phosphoric acid, boric acid, and an additive; the mass ratio of each component is: pure water 96.5% - 97%, ammonium adipate 1.6% - 1.8%, phosphoric acid 0.8% - 1.0%, boric acid 0.3% - 0.4%, additive aqueous solution 0.2% - 0.4%; the additive is citric acid, phosphate ester, phenol, or isopropanol.

[0011] As an optimization, the first impregnating solution described in step (4) is composed of the following raw materials by weight percentage: 10% - 15% thiophene, 10% - 15% 3,4 - ethylenedioxythiophene, 70% - 80% ethanol.

[0012] As an optimization, the second impregnating solution is composed of the following raw materials by weight percentage: 35% - 45% thiophene derivative, 5% - 10% modified carbon microspheres, 45% - 60% N,N - dimethylformamide.

[0013] As an optimization, the thiophene derivative is one or more of thiophene - 3,4 - diol, 3 - thiophene methanol, 3,4 - bis(2 - hydroxyethyl)thiophene, or thiophene - 3 - ol.

[0014] As an optimization, the oxidizing solution described in step (5) is composed of the following raw materials by weight percentage: ammonium persulfate 10% - 20%, 37 wt% hydrochloric acid 1% - 5%, sodium dodecylbenzenesulfonate 10% - 12%, EVA 5% - 10%, isobutanol 53% - 74%.

[0015] As an optimization, the polymerization condition described in step (5) is: 40 - 80 °C.

[0016] As an optimization, the aging treatment described in step (6) is step - up voltage aging, which specifically includes the following steps: the first stage: at room temperature, 15 V for 30 min; the second stage: 80 - 90 °C, 30 V for 2 h; the third stage: 100 - 110 °C, 35 V for 1 h; the fourth stage: 120 - 130 °C, 40 V for 20 min.

[0017] As an optimization, the preparation method of the modified carbon microspheres is as follows: Mix glucose, sodium oleate, P123, and pure water for 2 - 3 h, transfer to a high-pressure reactor, react at 150 - 160 °C for 24 h, wash and dry, and then treat under nitrogen protection in a 500 °C tubular furnace for 2 - 3 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:(7.5 - 9.5):(0.45 - 0.65); the addition amount of pure water is 30 - 40 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid according to a mass ratio of 1:(0.5 - 0.7):(150 - 200) by ultrasonic for 2 - 3 h, continue to stir for 10 - 12 h, and obtain the modified carbon microspheres after filtration, washing, and drying.

[0018] The present invention also provides a solid-state capacitor prepared by the preparation method described in any one of the above.

[0019] Advantages of the present invention: (1) In the repair step, a dense oxide film is formed through the conductivity of the formation solution, defects are reduced, the breakdown voltage ability of the product is improved, the oxide film is repaired, and the leakage current phenomenon of the product is reduced.

[0020] (2) In the aging process, different voltages are applied at normal temperature and high temperature for repair, so that the product can have good consistency in the leakage current during the overvoltage test, and the parameter differences are small.

[0021] (3) At the same time, through a double impregnation process - first, a highly conductive polymer substrate is formed by thiophene and PEDOT, and then a three-dimensional conductive network is constructed by introducing thiophene derivatives and modified carbon microspheres; borate bonds are introduced on the surface of the modified carbon microspheres through π-π stacking, and reversible borate bonds are formed with thiophenol, which not only fixes polythiophene on the surface of the carbon microsphere skeleton through covalent bonds, but also can be quickly recombined after local fracture under the impact of high-frequency current, maintaining the integrity of the three-dimensional conductive network, realizing interface self-repair, prolonging the service life of the solid-state capacitor, and being expected to be applied to high-frequency scenarios. Detailed implementation manners

[0022] To make the above objects, features, and advantages of the present invention more obvious and understandable, the following describes the detailed implementation manners of the present invention in conjunction with the embodiments of the specification.

[0023] Many specific details are set forth in the following description in order to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein. Those skilled in the art can make similar extensions without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below.

[0024] Secondly, the "one embodiment" or "embodiment" referred to herein means specific features, structures or characteristics that may be included in at least one implementation manner of the present invention. The "in one embodiment" that appears in different places in this specification does not all refer to the same embodiment, nor is it an individual or selectively mutually exclusive embodiment with other embodiments.

[0025] The glucose used in the present invention is α-D-glucose, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the P123 used is PEO-PPO-PEO, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the EVA is ethylene-vinyl acetate copolymer, with the brand name Levapren 500; the rest of the raw materials are also commonly commercially available in the art without special instructions.

[0026] Example 1, this example provides a preparation method of a solid-state capacitor, specifically: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.45 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2) Repair step: Immerse the core package in the formation solution for repair treatment; the formation solution contains pure water, ammonium adipate, phosphoric acid, boric acid and an additive; the mass ratio of each component is: pure water 96.5%, ammonium adipate 1.8%, phosphoric acid 1.0%, boric acid 0.4%, additive aqueous solution 0.3%; the additive is phosphate ester; (3) Drying step: Dry the core package in step (2); (4) Impregnation step: Immerse the core package in step (3) in the first impregnation solution for impregnation treatment; dry it; immerse it in the second impregnation solution for impregnation treatment and dry it; the first impregnation solution is composed of the following raw materials by weight percentage: 10% thiophene, 10% 3,4-ethylenedioxythiophene, 80% ethanol; the second impregnation solution is composed of the following raw materials by weight percentage: 35% thiophene derivative, 5% modified carbon microspheres, 60% N,N-dimethylformamide; the thiophene derivative is 3-thiophene methanol; the preparation method of the modified carbon microspheres is: Mix glucose, sodium oleate, P123 and pure water for 3 h, transfer to a high-pressure reaction kettle, react at 160 °C for 24 h, wash and dry, and then treat under a nitrogen protection and a 500 °C tubular furnace for 3 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:7.5:0.45; the addition amount of pure water is 30 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid in a mass ratio of 1:0.5:150 by ultrasonic for 3 h, then continue to stir for 12 h, and obtain modified carbon microspheres after filtration, washing and drying; (5) Polymerization step: Immerse the core package obtained in step (4) into the oxidation solution for polymerization; the polymerization conditions are: 80 °C; the oxidation solution is composed of the following raw materials by weight percentage: ammonium persulfate 10%, 37 wt% hydrochloric acid 1%, sodium dodecylbenzenesulfonate 10%, EVA 5%, isobutanol 74%; (6) Assembly of the waist and aging treatment; the aging treatment is stepwise voltage-up aging, which specifically includes the following steps: First stage: at room temperature, 15 V for 30 min; Second stage: 90 °C, 30 V for 2 h; Third stage: 110 °C, 35 V for 1 h; Fourth stage: 130 °C, 40 V for 20 min.

[0027] Example 2. This example provides a method for preparing a solid-state capacitor, specifically: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.6 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2) Repair step: Immerse the core package into the formation solution for repair treatment; the formation solution contains pure water, ammonium adipate, phosphoric acid, boric acid and an additive; the mass ratio of each component is: pure water 96.7%, ammonium adipate 1.7%, phosphoric acid 0.9%, boric acid 0.35%, additive aqueous solution 0.35%; the additive is citric acid; (3) Drying step: Dry the core package obtained in step (2); (4) Impregnation step: Immerse the core package obtained in step (3) into the first impregnation solution for impregnation treatment; dry it; immerse it into the second impregnation solution for impregnation treatment, and dry it; the first impregnation solution is composed of the following raw materials by weight percentage: 12% thiophene, 12% 3,4-ethylenedioxythiophene, 76% ethanol; the second impregnation solution is composed of the following raw materials by weight percentage: 40% thiophene derivative, 7% modified carbon microspheres, 53% N,N-dimethylformamide; the thiophene derivative is thiophene-3,4-diol; the preparation method of the modified carbon microspheres is: Mix glucose, sodium oleate, P123, and pure water for 2.5 h, transfer it to a high-pressure reaction kettle, react at 155 °C for 24 h, wash and dry, and then treat it in a nitrogen-protected 500 °C tubular furnace for 2.5 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:8:0.5; the addition amount of pure water is 35 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid according to the mass ratio of 1:0.6:170 by ultrasonic for 2.5 h, then continue to stir for 11 h, and obtain modified carbon microspheres after filtration, washing and drying; (5) Polymerization step: Immerse the core package obtained in step (4) into the oxidation solution, then take it out and dry it at 60 °C for polymerization; the oxidation solution consists of the following raw materials by weight percentage: ammonium persulfate 15%, 37 wt% hydrochloric acid 5%, sodium dodecylbenzenesulfonate 11%, EVA 7%, isobutanol 62%; (6) Assembly of the waist and aging treatment; the aging treatment is stepwise voltage-up aging, which specifically includes the following steps: First stage: at room temperature, 15V for 30 min; Second stage: 85 °C, 30V for 2 h; Third stage: 105 °C, 35V for 1 h; Fourth stage: 125 °C, 40V for 20 min.

[0028] Example 3, this example provides a preparation method of a solid-state capacitor, specifically: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.7 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2) Repair step: Immerse the core package into the formation solution for repair treatment; the formation solution contains pure water, ammonium adipate, phosphoric acid, boric acid and an additive; the mass ratio of each component is: pure water 97%, ammonium adipate 1.6%, phosphoric acid 0.8%, boric acid 0.3%, additive aqueous solution 0.3%; the additive is phenol; (3) Drying step: Dry the core package obtained in step (2); (4) Impregnation step: Immerse the core package obtained in step (3) into the first impregnation solution for impregnation treatment; dry it; immerse it into the second impregnation solution for impregnation treatment, and dry it; the first impregnation solution consists of the following raw materials by weight percentage: 15% thiophene, 15% 3,4-ethylenedioxythiophene, 70% ethanol; the second impregnation solution consists of the following raw materials by weight percentage: 45% thiophene derivative, 10% modified carbon microspheres, 45% N,N-dimethylformamide; the thiophene derivative is thiophene-3-ol; the preparation method of the modified carbon microspheres is: Mix glucose, sodium oleate, P123 and pure water for 2 h, transfer it to a high-pressure reaction kettle, react at 150 °C for 24 h, wash and dry it, and then treat it in a nitrogen-protected 500 °C tubular furnace for 2 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:9.5:0.65; the addition amount of pure water is 40 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid according to the mass ratio of 1:0.7:200 by ultrasonic for 2 h, then continue to stir for 10 h, and obtain the modified carbon microspheres after filtration, washing and drying; (5) Polymerization step: Immerse the core package obtained in step (4) into the oxidation solution for polymerization; the polymerization conditions are: 40 °C; the oxidation solution consists of the following raw materials by weight percentage: ammonium persulfate 20%, 37 wt% hydrochloric acid 5%, sodium dodecylbenzenesulfonate 12%, EVA 10%, isobutanol 53%; (6) Assembly of the waistband and aging treatment; the aging treatment is stepwise voltage-increasing aging, specifically including the following steps: First stage: at room temperature, 15 V for 30 min; Second stage: 80 °C, 30 V for 2 h; Third stage: 100 °C, 35 V for 1 h; Fourth stage: 120 °C, 40 V for 20 min.

[0029] Example 4. This example provides a method for preparing a solid-state capacitor, specifically: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.7 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2) Repair step: Immerse the core package into the formation solution for repair treatment; the formation solution contains pure water, ammonium adipate, phosphoric acid, boric acid and an additive; the mass ratio of each component is: pure water 97%, ammonium adipate 1.6%, phosphoric acid 0.8%, boric acid 0.3%, additive aqueous solution 0.3%; the additive is isopropanol; (3) Drying step: Dry the core package obtained in step (2); (4) Impregnation step: Immerse the core package obtained in step (3) into the first impregnation solution for impregnation treatment; dry it; immerse it into the second impregnation solution for impregnation treatment, and dry it; the first impregnation solution consists of the following raw materials by weight percentage: 15% thiophene, 15% 3,4-ethylenedioxythiophene, 70% ethanol; the second impregnation solution consists of the following raw materials by weight percentage: 45% thiophene derivative, 10% modified carbon microspheres, 45% N,N-dimethylformamide; the thiophene derivative is obtained by mixing thiophene-3,4-diol and 3-thiophene methanol with a mass ratio of 1:1; the preparation method of the modified carbon microspheres is: Mix glucose, sodium oleate, P123 and pure water for 2.3 h, transfer it to a high-pressure reaction kettle, react at 157 °C for 24 h, wash and dry it, and then treat it in a nitrogen-protected 500 °C tube furnace for 2.8 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:7.2:0.6; the addition amount of pure water is 37 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid according to a mass ratio of 1:0.55:155 by ultrasonic for 2 h, then continue to stir for 11 h, and obtain modified carbon microspheres after filtration, washing and drying; (5) Polymerization step: Immerse the core package obtained in step (4) into the oxidation solution for polymerization; the polymerization conditions are: 40 °C; the oxidation solution is composed of the following raw materials by weight percentage: ammonium persulfate 20%, 37 wt% hydrochloric acid 5%, sodium dodecylbenzenesulfonate 12%, EVA 10%, isobutanol 53%; (6) Assembly of the waistband and aging treatment; the aging treatment is stepwise voltage-up aging, specifically including the following steps: First stage: at room temperature, 15 V for 30 min; Second stage: 80 °C, 30 V for 2 h; Third stage: 100 °C, 35 V for 1 h; Fourth stage: 120 °C, 40 V for 20 min.

[0030] Comparative Example 1, the difference between this comparative example and Example 2 is that step (2) is omitted, and the core package obtained in step (1) is not subjected to the repair step. Specifically: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.6 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2) Drying step: Dry the core package obtained in step (1). (3) Impregnation step: Immerse the core package obtained in step (2) into the first impregnation solution for impregnation treatment; dry it; immerse it into the second impregnation solution for impregnation treatment, and dry it; the first impregnation solution is composed of the following raw materials by weight percentage: 12% thiophene, 12% 3,4-ethylenedioxythiophene, 76% ethanol; the second impregnation solution is composed of the following raw materials by weight percentage: 40% thiophene derivative, 7% modified carbon microspheres, 53% N,N-dimethylformamide; the thiophene derivative is thiophene-3,4-diol; the preparation method of the modified carbon microspheres is: Mix glucose, sodium oleate, P123, and pure water for 2.5 h, transfer it to a high-pressure reaction kettle, react at 155 °C for 24 h, wash and dry, and then treat it in a nitrogen-protected 500 °C tubular furnace for 2.5 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:8:0.5; the addition amount of pure water is 35 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid according to the mass ratio of 1:0.6:170 by ultrasonic for 2.5 h, then continue to stir for 11 h, and obtain modified carbon microspheres after filtration, washing, and drying; (4) Polymerization step: Immerse the core package obtained in step (3) into the oxidation solution and then take it out, and dry and polymerize it at 60 °C; the oxidation solution is composed of the following raw materials by weight percentage: ammonium persulfate 15%, 37 wt% hydrochloric acid 5%, sodium dodecylbenzenesulfonate 11%, EVA 7%, isobutanol 62%; (5) Assembly of the waist and aging treatment; the aging treatment is step-up voltage aging, specifically including the following steps: The first stage: treatment at normal temperature and 15V for 30 minutes; the second stage: treatment at 85°C and 30V for 2 hours; the third stage: treatment at 105°C and 35V for 1 hour; the fourth stage: treatment at 125°C and 40V for 20 minutes.

[0031] The processes of the remaining steps are all referred to Example 2 to obtain the solid-state capacitor of this comparative example.

[0032] Comparative Example 2. The difference between this comparative example and Example 2 is that it does not contain modified carbon microspheres. Specifically: (1) Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.6 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2) Repair step: Immerse the core package in the formation solution for repair treatment; the formation solution contains pure water, ammonium adipate, phosphoric acid, boric acid, and an additive; the mass ratio of each component is: pure water 96.7%, ammonium adipate 1.7%, phosphoric acid 0.9%, boric acid 0.35%, additive aqueous solution 0.35%; the additive is citric acid; (3) Drying step: Dry the core package obtained in step (2); (4) Impregnation step: Immerse the core package obtained in step (3) in the first impregnation solution for impregnation treatment; dry it; immerse it in the second impregnation solution for impregnation treatment, and dry it; the first impregnation solution is composed of the following raw materials by weight percentage: 12% thiophene, 12% 3,4-ethylenedioxythiophene, 76% ethanol; the second impregnation solution is composed of the following raw materials by weight percentage: 40% thiophene derivative, 60% N,N-dimethylformamide; the thiophene derivative is thiophene-3,4-diol; (5) Polymerization step: Immerse the core package obtained in step (4) in the oxidation solution and then take it out, and dry and polymerize it at 60°C; the oxidation solution is composed of the following raw materials by weight percentage: 15% ammonium persulfate, 5% 37 wt% hydrochloric acid, 11% sodium dodecylbenzenesulfonate, 7% EVA, 62% isobutanol; (6) Assembly of the waist and aging treatment; the aging treatment is step-up voltage aging, specifically including the following steps: The first stage: treatment at normal temperature and 15V for 30 minutes; the second stage: treatment at 85°C and 30V for 2 hours; the third stage: treatment at 105°C and 35V for 1 hour; the fourth stage: treatment at 125°C and 40V for 20 minutes.

[0033] The processes of the remaining steps are all referred to Example 2 to obtain the solid-state capacitor of this comparative example.

[0034] Comparative Example 3. The difference between this comparative example and Example 2 is that it does not contain thiophenol. Specifically: (1)Core package winding: Insert electrolytic paper between the anode foil and the cathode foil and wind it into a core package; the density of the electrolytic paper is 0.6 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber; (2)Repair step: Immerse the core package in the formation solution for repair treatment; the formation solution contains pure water, ammonium adipate, phosphoric acid, boric acid and additives; the mass ratio of each component is: pure water 96.7%, ammonium adipate 1.7%, phosphoric acid 0.9%, boric acid 0.35%, additive aqueous solution 0.35%; the additive is citric acid; (3)Drying step: Dry the core package obtained in step (2); (4)Impregnation step: Immerse the core package obtained in step (3) in the first impregnation solution for impregnation treatment; dry it; immerse it in the second impregnation solution for impregnation treatment and dry it; the first impregnation solution consists of the following raw materials by weight percentage: 12% thiophene, 12% 3,4-ethylenedioxythiophene, 76% ethanol; the second impregnation solution consists of the following raw materials by weight percentage: 40% thiophene derivative, 7% modified carbon microspheres, 53% N,N-dimethylformamide; the thiophene derivative is thiophene; the preparation method of the modified carbon microspheres is: Mix glucose, sodium oleate, P123 and pure water for 2.5 h, transfer to a high-pressure reaction kettle, react at 155 °C for 24 h, wash and dry, and then treat under nitrogen protection in a 500 °C tubular furnace for 2.5 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:8:0.5; the addition amount of pure water is 35 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1-pyreneboronic acid according to a mass ratio of 1:0.6:170 by ultrasonic for 2.5 h, then continue to stir for 11 h, and obtain modified carbon microspheres after filtration, washing and drying; (5)Polymerization step: Immerse the core package obtained in step (4) in the oxidation solution and then take it out, dry and polymerize at 60 °C; the oxidation solution consists of the following raw materials by weight percentage: ammonium persulfate 15%, 37 wt% hydrochloric acid 5%, sodium dodecylbenzenesulfonate 11%, EVA 7%, isobutanol 62%; (6)Assembly, waist binding and aging treatment; the aging treatment is step-up voltage aging, which specifically includes the following steps: The first stage: at room temperature, 15 V for 30 min; the second stage: 85 °C, 30 V for 2 h; the third stage: 105 °C, 35 V for 1 h; the fourth stage: 125 °C, 40 V for 20 min.

[0035] The processes of the remaining steps are all referred to Example 2 to obtain the solid-state capacitor of this comparative example.

[0036] The performance tests were carried out on the solid-state capacitors prepared by the examples and comparative examples with 25V and 220μF, including the initial capacitance CAP, equivalent series resistance ESR, leakage current, and the average retention rate of capacitance after 3000 cycles. The results are shown in Table 1.

[0037] Table 1 CAP (μF) ESR (mΩ) Leakage current (μA) Retention rate (%) Example 1 225 12 37 97.5 Example 2 228 14 37 96.8 Example 3 230 10 40 98.2 Example 4 229 11 39 98.0 Comparative Example 1 219 26 107 82.3 Comparative Example 2 224 31 93 79.5 Comparative Example 3 220 32 84 76.6 As can be seen from Table 1, the beneficial effects of the present invention are as follows: (1) In the repair step, a dense oxide film is formed through the conductivity of the formation solution, defects are reduced, the breakdown voltage ability of the product is improved, the oxide film is repaired, and the leakage current phenomenon of the product is reduced. The aging process is repaired by applying different voltages at room temperature and high temperature simultaneously, so that the product can obtain good consistency in the leakage current during the overvoltage test, and the parameter differences are small. At the same time, through the double impregnation process - first, a highly conductive polymer substrate is formed by thiophene and PEDOT, and then a three-dimensional conductive network is constructed by introducing thiophene derivatives and modified carbon microspheres; borate bonds are introduced on the surface of the modified carbon microspheres through π-π stacking interactions to form reversible borate bonds with thiophenol, which not only fixes polythiophene on the surface of the carbon microsphere skeleton through covalent bonds, but also quickly recombines after local fracture under the impact of high-frequency current to maintain the integrity of the three-dimensional conductive network, realizing interface self-repair, prolonging the service life of solid-state capacitors, and being expected to be applied to high-frequency scenarios.

[0038] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present invention, and they should all be covered by the scope of the claims of the present invention.

Claims

1. A method for preparing a solid-state capacitor, characterized in that, The preparation method includes the following steps: (1) Core wrapping: Insert electrolytic paper between the anode foil and the cathode foil and wind them into a core package; (2) Repair step: Immerse the core package in a formation solution for repair treatment; (3) Drying step: Dry the core package obtained in step (2); (4) Impregnation step: Immerse the core package obtained in step (3) in a first impregnation solution for impregnation treatment; dry it; then immerse it in a second impregnation solution for impregnation treatment and dry it; (5) Polymerization step: Immerse the core package obtained in step (4) in an oxidation solution for polymerization; (6) Assembly of the waist and aging treatment.

2. The preparation method of a solid-state capacitor according to claim 1, characterized in that, The density of the electrolytic paper described in step (1) is 0.45 - 0.7 g / cm 3 , the thickness is 50 μm, and the raw material is Manila hemp fiber.

3. The preparation method of a solid-state capacitor according to claim 1, wherein, The formation solution described in step (2) contains pure water, ammonium adipate, phosphoric acid, boric acid, and an additive; the mass ratio of each component is: pure water 96.5% - 97%, ammonium adipate 1.6% - 1.8%, phosphoric acid 0.8% - 1.0%, boric acid 0.3% - 0.4%, additive aqueous solution 0.2% - 0.4%; the additive is citric acid, phosphate ester, phenol, or isopropanol.

4. The manufacturing method of a solid-state capacitor as described in claim 1, characterized in that, The first impregnation solution described in step (4) consists of the following raw materials by weight percentage: 10% - 15% thiophene, 10% - 15% 3,4 - ethylenedioxythiophene, 70% - 80% ethanol; The second impregnation solution consists of the following raw materials by weight percentage: 35% - 45% thiophene derivative, 5% - 10% modified carbon microspheres, 45% - 60% N,N - dimethylformamide; The thiophene derivative is one or more of thiophene - 3,4 - diol, 3 - thiophene methanol, 3,4 - bis(2 - hydroxyethyl)thiophene, or thiophene - 3 - ol.

5. The manufacturing method of a solid-state capacitor according to claim 1, characterized in that, The oxidation solution described in step (5) consists of the following raw materials by weight percentage: 10% - 20% ammonium persulfate, 1% - 5% 37wt% hydrochloric acid, 10% - 12% sodium dodecylbenzenesulfonate, 5% - 10% EVA, 53% - 74% isobutanol.

6. The preparation method of a solid-state capacitor according to claim 1, wherein The polymerization conditions in step (5) are: 40 - 80°C.

7. The manufacturing method of a solid-state capacitor as claimed in claim 1, characterized in that, The aging treatment described in step (6) is step - up voltage aging, which specifically includes the following steps: The first stage: at room temperature, 15V for 30 min; the second stage: 80 - 90°C, 30V for 2 h; the third stage: 100 - 110°C, 35V for 1 h; the fourth stage: 120 - 130°C, 40V for 20 min.

8. The preparation method of a solid-state capacitor according to claim 4, wherein, The preparation method of the modified carbon microspheres is as follows: Mix glucose, sodium oleate, P123, and pure water for 2 - 3 h, transfer it to a high - pressure reaction kettle, react at 150 - 160°C for 24 h, wash and dry it, and then treat it in a nitrogen - protected 500°C tubular furnace for 2 - 3 h to obtain hollow carbon nanospheres; the molar ratio of glucose, sodium oleate, and P123 is 1:(7.5 - 9.5):(0.45 - 0.65); P123 is PEO - PPO - PEO; the addition amount of pure water is 30 - 40 times that of glucose; Mix the hollow carbon nanospheres, tetrahydrofuran, and 1 - pyreneboronic acid according to the mass ratio of 1:(0.5 - 0.7):(150 - 200) by ultrasonic for 2 - 3 h to mix evenly, then continue to stir for 10 - 12 h, and obtain the modified carbon microspheres after filtration, washing, and drying.

9. A solid-state capacitor, characterized in that, It is prepared by the preparation method described in any one of claims 1 - 8.

Citation Information

Patent Citations

  • High-reliability solid electrolytic capacitor manufacturing method

    CN102867651A

  • Manufacturing method for aluminum electrolytic capacitor

    CN105931862A

  • Aging treatment method for aluminum electrolytic capacitor

    CN108648914A

  • Solid aluminum electrolytic capacitor with self-repair function and preparation method of solid aluminum electrolytic capacitor

    CN108878152A

  • Capacitor aging method

    CN110875148A

Cited By

  • High-temperature-resistant solid-state capacitor and preparation method thereof

    CN120998689A

  • High temperature resistant solid state capacitor and method of making same

    CN120998689B

  • Manufacturing method of aluminum electrolytic capacitor core

    CN121964388A